Broadband Adiabatic Couplers in Thin-Film Lithium Niobate on Insulator - Lin, Yi Xin; Younesi, Mohammadreza; Chung, Hung Pin; Chiu, Hua Kung; Geiss, Reinhard; Tseng, Quan Hsiang; Setzpfandt, Frank; Pertsch, Thomas; Chen, Yen Hung (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We demonstrate broadband adiabatic couplers using lithium niobate on insulator (LNOI) waveguides with a footprint reduced by 98% relative to bulk LN devices. LNOI couplers with coupling efficiency >95% across telecom S-C-L bands are obtained.
CRIS-Team Scopus Importer:2023-04-20